# Explain the error made in solving the equation below. Then solve the equation correctly.?

Explain the error made in solving the equation below. Then solve the equation correctly.

(x + 2)(x – 3) = 6

x + 2 = 6 x – 3 = 6

x = 4 x = 9

Relevance

You can only solve that way when the equation = 0

Since it equals 6, you need to work it out again:

x^2 +2x - 3x - 6 = 6

x^2 - x - 12 = 0

(x - 4)(x + 3) = 0

x = 4

x = -3

• Anonymous
10 years ago

Another equals was added. That is the mistake, not to mention the random adding of a six next to the second x.

(x + 2)(x - 3) = x^2 - x - 6

x^2 - x - 6 - 6 = 0

x^2 - x - 12 = 0

(x + 3)(x - 4)

• Thats not even remotely correct, I don't know what the person was trying to do. But I can show you how it should be done.

(x+2)(x-3) = 6

x^2 - x - 6 = 6

x^2 - x - 12 = 0

(x-4)(x+3) = 0

x = -3, 4

Source(s): Haha this kind of math makes me nostalgic :P
• Anonymous
10 years ago

x + 2 not equals 6

x - 3 not equals 6

only works if (x+2)(x - 3) = 0

Solve: FOIL it out.

x^2 - x - 6 = 6

x^2 - x - 12 = 0

(x - 4)(x + 3) = 0

x - 4 = 0 : x + 3 = 0

x = 4, -3